ON COMPUTATIONAL DIFFERENCES OF CRITICAL POINTS ON EQUILIBRIUM CURVE - Gaik A. Manuylov; Sergey B. Kosytsyn; Maxim M. Begichev (International Journal for Computational Civil and Structural Engineering, 2017)
In this paper, we discuss the features of investigating the type of the critical point on the equilibrium curve (bifurcation point or limit point). There are new ideas about the completion of the initial equilibrium at the limit point or bifurcation point. Examples as the Mises farm, a shallow arch and a shallow cylindrical panel show shows the features of the birth and movement of bifurcation points along the curve of equilibrium.